Collaborative design methodologies for clothing flat modeling (Revista de Ensino em Artes, Moda e Design, 2020)
This article reflects on the importance of collaborative design methodologies in the construction of new configurations for teaching flat clothing modeling. Within the field of teaching fashion and clothing, but specifically in the disciplines of flat modeling, several problems can be identified regarding teaching-learning. Silva and França (2018) state that there is little perceived ability to understand the execution of the molds on the part of the students, which cause the discipline to be seen with a high degree of complexity, causing dissatisfaction, both on the part of the students and by part of the teachers who teach it. This article is based on data, four surveys carried out in fashion and clothing courses in Brazil regarding teaching-learning of the flat modeling technique and from the gaps identified in its results, we will substantiate the paths taken by this research.Based on the assumption that the understanding of the reasons and the difficulties present in the contexts of the researches carried out on teaching and learning of flat modeling in recent years, are not due to individual and solitary actions, but to collective constructions of all the authors involved. In this work, concepts of collaborative design methodologies are explored, as innovative and effective methods of this construction. Understanding that, through collaborative means, it is possible to contribute with activities and solutions from different fields, starting from a new perspective when conceiving formal concepts and solutions.Thus, the question that guides this study and which will be answered is: how can collaborative design methodologies contribute to the flat modeling of clothing? The article is structured in four topics, which aims to clarify points and difficulties raised in research that were carried out in recent years on teaching and learning of flat modeling through a systematic literature review that points out data on the state of the art of flat modeling and its relationship with collaborative methodologies.